The Routledge handbook of disability and sexuality - Shuttleworth, Russell; Mona, Linda (Routledge, 2021)
This handbook provides a much-needed holistic overview of disability and sexuality research andscholarship. With authors from a wide range of disciplines and representing a diversity of nationalities, it provides a multi-perspectival view that fully captures the diversity of issues and outlooks. Organised into six parts, the contributors explore long-standing issues such as the psychological, interpersonal, social, political and cultural barriers to sexual access that idsabled people face and their struggle for sexual rights and participation. The volume also engages issues that have been on the periphery of the discourse, such as sexual accomodations and support aimed at facilitating disabled people's sexual well-being; the socio-sexual tensions confronting disabled people with intersecting stigmatised identities such as LGBTBI or asexual; and the sexual concerns of disabled people in the Global South. It interrogates disability and sexuality from diverse perspectives, from more traditional psychological and sociological models, to various subversive and post-theoretical perspectives and queer theory. This handbook examines the cutting-edge, and sometimes ethically contentious, concerns that have been repressed in the field. With current, international and comprehensive content, this book is essential reading for students, academics and researchers in the areas of disability, gender and sexuality, as well as applied disciplines such as healthcare pratictionners, counsellors, psychology trainees and social workers.
Le texte Santinele Martino, A. et Fudge Schormans, A. (2021). Theoretical developments: Queer theory meets crip theory a été donné en lecture au cours SEX1920
Keywords: EDI; LGBTQIA2+; accessibilité; approches et analyses; capacitisme; care; corps; cours; discipline; histoire et politique; identités LGBTQIA2+; intersectionnalité; outils; ouvrages de références; premier cycle; ressource en ligne; santé; sciences de la santé; sciences humaines; sex1911; sex1920; sexologie; sexualité; systèmes d'oppressions; thématiques; travail social; études critiques du handicap

Companion to sexuality studies - Naples, Nancy A. (Wiley Blackwell, 2020)
An inclusive and accessible resource on the interdisciplinary study of gender and sexuality Companion to Sexuality Studies explores the significant theories, concepts, themes, events, and debates of the interdisciplinary study of sexuality in a broad range of cultural, social, and political contexts. Bringing together essays by an international team of experts from diverse academic backgrounds, this comprehensive volume provides original insights and fresh perspectives on the history and institutional regulatory processes that socially construct sex and sexuality and examines the movements for social justice that advance sexual citizenship and reproductive rights. Detailed yet accessible chapters explore the intersection of sexuality studies and fields such as science, health, psychology, economics, environmental studies, and social movements over different periods of time and in different social and national contexts. Divided into five parts, the Companion first discusses the theoretical and methodological diversity of sexuality studies.Subsequent chapters address the fields of health, science and psychology, religion, education and the economy. They also include attention to sexuality as constructed in popular culture, as well as global activism, sexual citizenship, policy, and law. An essential overview and an important addition to scholarship in the field, this book: Draws on international, postcolonial, intersectional, and interdisciplinary insights from scholars working on sexuality studies around the world Provides a comprehensive overview of the field of sexuality studies Offers a diverse range of topics, themes, and perspectives from leading authorities Focuses on the study of sexuality from the late nineteenth century to the present Includes an overview of the history and academic institutionalization of sexuality studies The Companion to Sexuality Studies is an indispensable resource for scholars, researchers, instructors, and students in gender, sexuality, and feminist studies, interdisciplinary programs in cultural studies, international studies, and human rights, as well as disciplines such as anthropology, psychology, history, education, human geography, political science, and sociology.
Keywords: LGBTQIA2+; anthropologie; approches et analyses; cours; discipline; féminisme décolonial; premier cycle; psychologie; queer; santé; sciences humaines; sexologie; sexualité; soc2014; sociologie; thématiques; études de genres; études des sexualités

The social construction of sexuality - Seidman, Steven (W.W. Norton & Company, 2015)
In The Social Construction of Sexuality, Steven Seidman investigates the political and social consequences of privileging certain sexual practices and identities while stigmatizing others. Addressing a range of topics from gay and lesbian identities to sex work, Seidman delves into issues of social control that inform popular beliefs and moral standards. The new Third Edition features three new chapters that focus on the changing cultures of intimacy, the promise and perils of cyber intimacies, and youth struggles to negotiate independence and intimate solidarity.– Provided by Publisher.
Section: xv, 301 pages ; 21 cm
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; hétérosexisme; intimité; premier cycle; privilèges; sciences humaines; sexologie; sexualité; soc2014; systèmes d'oppressions; thématiques; travail; travail du sexe

Sexualité - Weeks, Jeffrey; Mendès-Leite, Rommel; Collomb-Boureau, Colette; Millet, Baudoin; Baudry, Samuel (Presses universitaires de Lyon, 2014)
Première traduction française d’un ouvrage de Jeffrey Weeks, ce « manifeste intellectuel » est d’ores et déjà un classique anglo-saxon depuis plus de vingt ans. Dès sa première édition, il s’est imposé comme une introduction de pointe aux débats sur les sexualités, le genre et l’intime. Jeffrey Weeks retrace l’histoire de la sexualité, pensée comme une construction sociale, façonnée et remodelée inlassablement par le contexte dans lequel elle existe et s’exprime : la sexualité n’est ni naturelle ni uniforme, mais culturelle et plurielle. Cette approche pionnière permet de couvrir un large champ d’investigation : les traditions religieuses, les politiques identitaires, la mondialisation, l’impact social du sida, l’influence de la génétique et de la psychanalyse, la lutte des sexes, les nouveaux modèles familiaux... Désormais, dans sa troisième édition (qui fait l’objet de cette traduction), cet essai majeur intègre de nouveaux concepts et enjeux, issus en particulier des mouvements LGBT et des débats sur le mariage homosexuel.
Section: 1 vol. (303 p.) : couv. ill. en coul. ; 18 cm.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; discours dominant; histoire; histoire et politique; hétérosexisme; patriarcat; premier cycle; queer; sciences humaines; sexologie; sexualité; soc2014; systèmes d'oppressions; thématiques

La régulation sociale des minorités sexuelles: l'inquiétude dela différence - Corriveau, Patrice; Daoust, Valérie; ProQuest (Firme) (Les Presses de l'Université du Québec, 2011)
Successivement condamnées par la religion, criminalisées par le droit pénal et finalement médicalisées, les minorités sexuelles ont subi une forte répression institutionnelle. Depuis, les luttes des mouvements gais et lesbiens ont conduit, dans certains pays, à la reconnaissance des droits des homosexuels au mariage et à la parentalité. Toutefois, l’homosexualité est encore trop souvent perçue comme une menace à la tradition et à l’ordre « naturel ». Réunissant les contributions de chercheurs en sociologie, en philosophie, en criminologie, en histoire, en anthropologie, en sexologie et en travail social, cet ouvrage porte sur les multiples modes de régulation institutionnelle et sociale des minorités sexuelles. Tout en exposant les différentes pratiques de répression employées par le passé, les auteurs traitent de sujets contemporains comme l’homophobie dans les écoles et l’homoparentalité. Soulevant des questions de justice sociale, ils rappellent que tous, gais et lesbiennes y compris, sont engagés dans le processus de régulation des minorités sexuelles.
Keywords: LGBTQIA2+; amériques; anthropologie; approches et analyses; belgique; canada; cours; criminologie; discipline; europe; histoire; homophobie; hétérosexisme; justice sociale; militance; philosophie; premier cycle; queer; québec; régions géographiques; santé; sciences humaines; sexologie; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques; travail social; études gaies et lesbiennes

Queer Diagnoses: Parallels and Contrasts in the History of Homosexuality, Gender Variance, and the Diagnostic and Statistical Manual - Drescher, Jack (Archives of Sexual Behavior : The Official Publication of the International Academy of Sex Research, 2010)
The American Psychiatric Association (APA) is in the process of revising its Diagnostic and Statistical Manual (DSM), with the DSM-V having an anticipated publication date of 2012. As part of that ongoing process, in May 2008, APA announced its appointment of the Work Group on Sexual and Gender Identity Disorders (WGSGID). The announcement generated a flurry of concerned and anxious responses in the lesbian, gay, bisexual, and transgender (LGBT) community, mostly focused on the status of the diagnostic categories of Gender Identity Disorder (GID) (for both children and adolescents and adults). Activists argued, as in the case of homosexuality in the 1970s, that it is wrong to label expressions of gender variance as symptoms of a mental disorder and that perpetuating DSM-IV-TR’s GID diagnoses in the DSM-V would further stigmatize and cause harm to transgender individuals. Other advocates in the trans community expressed concern that deleting GID would lead to denying medical and surgical care for transgender adults. This review explores how criticisms of the existing GID diagnoses parallel and contrast with earlier historical events that led APA to remove homosexuality from the DSM in 1973. It begins with a brief introduction to binary formulations that lead not only to linkages of sexual orientation and gender identity, but also to scientific and clinical etiological theories that implicitly moralize about matters of sexuality and gender. Next is a review of the history of how homosexuality came to be removed from the DSM-II in 1973 and how, not long thereafter, the GID diagnoses found their way into DSM-III in 1980. Similarities and differences in the relationships of homosexuality and gender identity to psychiatric and medical thinking are elucidated. Following a discussion of these issues, the author recommends changes in the DSM-V and some internal and public actions that the American Psychiatric Association should take.
Keywords: LGBTQIA2+; amériques; approches et analyses; cours; discipline; inégalités; premier cycle; psychiatrie; régions géographiques; santé; sciences; sciences humaines; sexologie; soc2014; système médical; systèmes d'oppressions; thématiques; transidentité; violences; états-unis

Critical intersex - Holmes, Morgan (Ashgate, 2009)
To date, intersex studies has not received the scholarly attention it deserves as research in this area has been centred around certain key questions, scholars and geographical regions. Exploring previously neglected territories, this book broadens the scope of intersex studies, whilst adopting perspectives that turn the gaze of the liberal, humanist, scientific outlook upon itself, in order to reconfigure debates about rights, autonomy and subjectivity, and challenges the accepted paradigms of intersex identity politics. Presenting the latest theoretical and empirical research from an international group of experts, this is a truly interdisciplinary volume containing critical approaches from both the humanities and social sciences. With its contributions to sociology, anthropology, medicine, law, history, cultural studies, psychology and psychoanalysis, Critical Intersex will appeal to scholars and clinical practitioners alike.
Section: 1 vol. (XIV-257 p.) ; 24 cm.
Keywords: LGBTQIA2+; approches et analyses; corps; cours; discipline; intersexuation; inégalités; premier cycle; queer; santé; sciences humaines; sexologie; soc2014; système médical; systèmes d'oppressions; thématiques; violences; violences médicales; études intersexes

Intersections: cultures, sexualités et genres - Brotman, Shari L.; Lévy, Joseph J. (Presses de l'Université du Québec, 2008)
Les intersections entre la culture, le genre et la sexualité retiennent aujourd’hui l’attention des chercheurs qui travaillent sur la diversité sexuelle, une tendance que l’on rencontre dans l’espace québécois et canadien. Plusieurs études ont ainsi porté sur ces enjeux parmi les autochtones et les groupes ethnoculturels. Cet ouvrage collectif, réalisé par des chercheurs, anglophones et francophones, de l’équipe pancanadienne Sexualités, Vulnérabilités et Résilience, présente ainsi un ensemble de travaux qui font le point sur ces questions. Les dimensions théoriques et méthodologiques sont ainsi cernées et des études empiriques, faisant appel à des approches quantitatives et qualitatives, traitent des trajectoires et des identités parmi différentes populations, des problèmes de santé auxquels elles peuvent être confrontées et des variations dans les usages sociosexuels d’Internet. Ce tour d’horizon aide à mieux comprendre la complexité des intersections touchant les identités sexuelles et les dimensions culturelles et suggère des pistes de recherche et d’intervention à développer.
Section: xvi, 474 pages ; 23 cm
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; approches et analyses; canada; cours; discipline; identités LGBTQIA2+; intersectionnalité; premier cycle; psychologie; périodes historiques; queer; québec; ressource en ligne; régions géographiques; sciences humaines; sciences sociales; sex2283; sexologie; sexualité; thématiques; travail social

L'invention de l'hétérosexualité - Katz, Jonathan (EPEL, 2001)
L'auteur retrace l'histoire du concept d'hétérosexualité. Il analyse les textes d'auteurs comme Freud, Richard von Krafft-Ebing, Michel Foucault, Betty Friedan ou Kate Millet. Il nous montre que la distinction homosexuel/hétérosexuel ne repose pas sur une nature immuable mais constitue une façon récente de classer et de juger la société. [SDM].
Section: 236 pages ; 21 cm
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; LGBTQIA2+; analyse de discours; approches et analyses; cours; discipline; discours dominant; europe; france; his4860; histoire; histoire et politique; homosexualité; hétérosexisme; hétérosexualité; identité sexuelle; identités LGBTQIA2+; postmodernisme; premier cycle; périodes historiques; queer; rapports sociaux de sexe; régions géographiques; sciences humaines; sciences sociales; sex1181; sex1183; sexologie; sexualité; shm4000; soc2014; systèmes d'oppressions; thématiques; épistémologie

Marché au sexe - Rubin, Gayle; Butler, Judith P.; Sokol, Eliane (EPEL, 2001)
"Aucun amateur de cuisine épicée ne se verra privé de liberté ou victime d'ostracisme pour avoir satisfait ses papilles gustatives. En revanche, on peut être jeté en prison pour trop aimer les chaussures en cuir. De même, l'homosexualité, le sida, la pornographie, le transsexualisme, et aujourd'hui la pédophilie, donnent-ils lieu à ce que Gayle Rubin appelle une " panique sexuelle ". Chaque panique désigne une minorité sexuelle, généralement inoffensive, comme population-cible. Au terme du processus, celle-ci se trouve décimée, et la société tout entière, juridiquement et socialement, réorganisée. Gayle Rubin a jeté les bases d'un champ autonome d'études sur le sexe où désir, jouissance et diversité érotique, pourraient trouver leur raison théorique et politique. Les trois textes publiés ici s'inscrivent dans une filiation politique (le féminisme, la nouvelle gauche, les luttes antiracistes, les luttes pour les droits civiques) et théorique (les sexologues, Freud, Lacan, Marx, Foucault, Derrida). Les paradigmes ne valent rien sans l'enquête de terrain, et rien non plus s'ils ne s'actualisent en choix de stratégie et de tactique politiques. L'ensemble s'éclaire du partiel, le partiel de l'ensemble. Nous sommes loin ici du communautarisme béat qu'on prête parfois en France aux intellectuels américains. Qu'on lise les critiques acerbes de Judith Butler sur les replis identitaires : les lesbiennes n'ont rien d'autre en commun que leur expérience du sexisme et de l'homophobie. Ou ses réserves sur le coming out : " La sexualité reste-t-elle sexualité quand elle est soumise à un critère de transparence et de révélation? Une quelconque sexualité serait-elle possible sans cette opacité qui a pour nom inconscient? " Gayle Rubin et Judith Butler soulignent constamment la nécessité de ne pas troquer une violence contre une autre, une démonologie religieuse contre une démonologie laïque, laissant ainsi sa chance à l'érotologie moderne. (Éditeur).
Contenue: Entretien : Marché au sexe / Gayle S. Rubin et Judith Butler – Penser le sexe / Gayle S. Rubin – Imitation et insubordination du genre / Judith Butler.
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; anthropologie; approches et analyses; corps; cours; cycles supérieurs; discipline; fem1000; fem7000; hétérosexisme; identités LGBTQIA2+; lesbianisme; lit3220; philosophie; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; sex3383; sexologie; sexualité; soc2014; systèmes d'oppressions; thématiques; théories féministes; transféminisme; états-unis

Culture, society and sexuality: a reader - Parker, Richard G.; Aggleton, Peter (UCL Press, 1999)
Since the beginnings of time, people have been interested in sex - the form it takes, the pleasure it can give, the circumstances in which it occurs, and what it means - both for the individuals concerned and to society more generally. Often seen as a synonym for love, sometimes as an expression of power, and infrequently as a means of exploitation and abuse, sex is a complex and multi-faceted aspect of human behaviour that has been written about by numerous writers and theorists worldwide. This book offers an introduction to the central debates in sexuality research. Among the issues examined are the social and cultural dimensions of sex, human sexuality and sex research. It will be of use to students of sociology, cultural studies, and health and behavioural studies.
Keywords: LGBTQIA2+; VIH; approches et analyses; cours; discipline; hétérosexisme; identités LGBTQIA2+; premier cycle; queer; ressource en ligne; santé; sciences humaines; sex1920; sexisme; sexologie; sexualité; systèmes d'oppressions; thématiques

Inside the academy and out: lesbian/gay/queer studies and social action - Ristock, Janice L.; Taylor, Catherine G. (University of Toronto Press, 1998)
Inside the Academy and Out demonstrates that the pedagogical and theoretical insights offered by lesbian/gay/queer studies can have relevance to a broader social sphere. The essayists represented here come from a wide range of disciplines, including English, education, philosophy, sociology, and women's studies. Their essays are divided into two broad areas: 'Pedagogy and Research' and 'Spheres of Action.' Taken together, they explore teaching and research theory, examining their implications in areas such as AIDS education, social services, law reform, and popular culture.
Section: xi, 365 pages ; 24 cm
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; approches et analyses; cours; discipline; droit; ethnographie; intersectionnalité; justice sociale; militance; premier cycle; pédagogie; périodes historiques; queer; santé; science politique et droit; sciences de l'éducation; sciences humaines; sexologie; soc2014; thématiques; violences

New sexual agendas - Segal, Lynne (New York University Press, 1997)
"Taking on those who would limit sexual freedom, New Sexual Agendas challenges the notion that there are fixed sexual behaviors for men and women. This engaging collection draws on a number of disciplines including women's studies, literature, gender studies, cultural studies, history, politics, education, sociology, and psychology."
Section: xviii, 278 p
Keywords: LGBTQIA2+; approches et analyses; arts; corps; cours; discipline; histoire; histoire et politique; hétéronormativité; hétérosexisme; hétérosexualité; premier cycle; psychologie; queer; rapports sociaux de sexe; santé; sciences humaines; sexologie; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques; études de genre; études littéraires

Mapping desire: geographies of sexualities - Bell, David; Valentine, Gill (Routledge, 1995)
This is the first book to explore sexualities from a geographical perspective. The nature of place and notions of space are of increasing centrality to cultural and social theory. Mapping Desire presents the rich and diverse world of contemporary sexuality, exploring how the heterosexual body has been appropriated and resisted on the individual, community and city scales. The geographies presented here range across Europe, America, Australasia, Africa, the Pacific and the imaginary, cutting across city and country and analysing the positions of gay men, lesbians, bisexuals and heterosexuals. The contributors ring different interests and approaches to bear on theoretical and empirical material from a wide range of sources. The book is divided into four sections: cartographies/identities; sexualised spaces: global/local; sexualised spaces: local/global; sites of resistance. Each section is separately introduced. Beyond the bibliography, an annotated guide to further reading is also provided to help the reader map their own way through the literature.
Le texte de Binnie, Jon. 1995. « Trading places : consumption, sexuality and the production of queer space. » figure dans la bibliographie du cours SOC2014.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; géographie; hétéronormativité; hétérosexisme; premier cycle; queer; sciences humaines; sexologie; sexualité; soc2014; systèmes d'oppressions; thématiques

Un choix sans equivoque : recherches historiques sur les relations amoureuses entre les femmes : XVIe-XXe siecle - Bonnet, Marie-Jo (Denoël, 1981)
C'est le fruit de recherches menées pour une thèse de doctorat de 3e cycle. Etude détaillée, même érudite, mais de lecture facile. Importante bibliographie.
Section: 293 pages
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1999; LGBTQIA2+; amour lesbien; approches et analyses; cours; discipline; discours dominant; his4860; histoire; histoire de la sexualité; histoire des femmes*; histoire et politique; hétérosexisme; identités LGBTQIA2+; lesbianisme; lesbiennes; premier cycle; périodes historiques; rapports sociaux de sexe; relations amoureuses; régions géographiques; sciences humaines; sexisme; sexologie; sexualité; sexualité lesbienne; sexualités dissidentes; systèmes d'oppressions; thématiques